2012
DOI: 10.1002/cnm.1485
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–structure interaction simulations of the Fontan procedure using variable wall properties

Abstract: Children born with single ventricle heart defects typically undergo a staged surgical procedure culminating in a total cavopulmonary connection (TCPC) or Fontan surgery. The goal of this work was to perform physiologic, patient-specific hemodynamic simulations of two post-operative TCPC patients by using fluid-structure interaction (FSI) simulations. Data from two patients are presented, and post-op anatomy is reconstructed from MRI data. Respiration rate, heart rate, and venous pressures are obtained from cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…Considering the limited pulsatility in the Fontan circulation, the common assumptions of rigid walls and steady flow are valid. Furthermore, Long et al 25 showed in two patients that the time-averaged power efficiencies calculated with rigid walls were only 1.5% lower than that calculated with compliant walls.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the limited pulsatility in the Fontan circulation, the common assumptions of rigid walls and steady flow are valid. Furthermore, Long et al 25 showed in two patients that the time-averaged power efficiencies calculated with rigid walls were only 1.5% lower than that calculated with compliant walls.…”
Section: Discussionmentioning
confidence: 93%
“…Despite favorable short-term outcomes and lowered mortality rates (1,13,14,17,19), numerous long-term complications have been reported (8) including ventricular dysfunction and limited ventricular power (28), increased pulmonary vascular resistance (4), arrhythmias (6), severely diminished exercise capacity (21,24,31), protein losing enteropathy (22), and hepatic complications (4,9). Although considerable advances have been made in understanding total cavopulmonary connection (TCPC) hemodynamics (16,18,20,29,30) and in pre-operative surgical planning (26), therapies for improving cardiac hemodynamics and averting end-stage complications in the growing population of Fontan patients are currently lacking.…”
mentioning
confidence: 98%
“…Despite favorable short-term outcomes and lowered mortality rates (1,13,14,17,19), numerous long-term complications have been reported (8) including ventricular dysfunction and limited ventricular power (28), increased pulmonary vascular resistance (4), arrhythmias (6), severely diminished exercise capacity (21, 24, 31), protein losing enteropathy (22), and hepatic complications (4, 9). Although considerable advances have been made in understanding total cavopulmonary connection (TCPC) hemodynamics (16,18,20,29,30) and in pre-operative surgical planning (26), therapies for improving cardiac hemodynamics and averting end-stage complications in the growing population of Fontan patients are currently lacking.Of specific interest to this study are the effects of Fontan circulation on the liver and gastrointestinal (GI) tract. The altered series arrangement of the systemic and pulmonary circulations in the Fontan patient, together with the lack of a functional right heart to pump blood to the lungs, predisposes the systemic veins to higher pressures and in turn elevates hepatic venous pressure.…”
mentioning
confidence: 99%
“…Long et al 27 conducted an FSI study for two patient-specific extracardiac TCPC, dividing the domain of interest into multiple regions to account for the different material properties and wall thicknesses of the veins, arteries and artificial Fontan pathway. Comparing FSI and rigid wall results, local differences were noted in WSS but not in global measures, such as time averaged pressures, energy efficiency, or hepatic flow distribution.…”
Section: Outflow Boundary Conditionsmentioning
confidence: 99%